Contextualising challenges of reproduction and motherhood in Florence, Italy: a qualitative study. (2nd January 2020) - DeMaria, Andrea L.; Rivera, Sydney; Naoum, Zeina; Ramos-Ortiz, Jaziel; Meier, Stephanie; Dykstra, Chandler
Abstract: Objectives: This study sought to understand attitudes, behaviours and expectations regarding reproductive planning, infertility and motherhood among women living in Italy. Methods: Researchers conducted 55 in-depth interviews among 46 reproductive-aged women living in or around Florence, Italy, currently using the Italian health care system, and nine Italian health care professionals. Researchers used an expanded grounded theory approach to understand women's reproductive experiences, with the social-ecological model serving as a conceptual lens for data analyses. Results: Fertility care inadequacy and financial instability impacted participants' attitudes towards reproduction. Women's shifting roles and reduced marital salience prompted decisions to delay or forgo childbearing. For pregnant women and women with children, perceived postpartum challenges included employment discrimination, childrearing costs and variable paternal support. Some participants discussed increased parental responsibility sharing, but many noted lingering expectations that women prioritise motherhood above other pursuits. Conclusion: Findings provide insight into Italian women's reproductive attitudes and behaviours and the declining fertility rate in the current economic and social environment. Practical recommendations for policy and socio-cultural interventions should address reproductive barriers such as affordable childcare, improved fertility assistance, maternal employment protection, and better utilization of existing support structures.